Fetal and Maternal Risk Factors Caused by Antenatal Fetal Death in Women of Reproductive Age - Abdieva Nigina Ulugbekovna (American Journal of Bioscience and Clinical Integrity, 2025)
Annotation: Antenatal fetal death, defined as intrauterine demise occurring after 20 weeks of gestation, remains a major public health concern with profound emotional and clinical consequences for women of reproductive age. Despite advancements in prenatal care, the prevalence of stillbirth continues to reflect disparities in maternal health, access to care, and underlying medical conditions. This review aims to identify and analyze both fetal and maternal risk factors contributing to antenatal fetal death, highlighting existing knowledge gaps in early detection and prevention. A systematic literature review was conducted using databases such as PubMed, Scopus, and Google Scholar, focusing on studies from 2013 to 2023 that examined etiological factors and outcomes associated with intrauterine fetal demise. Findings consistently identified maternal hypertension, diabetes mellitus, obesity, thrombophilia, and infections as primary contributors, while fetal factors included congenital anomalies, growth restriction, and placental insufficiency. Socioeconomic status, inadequate antenatal visits, and advanced maternal age also emerged as significant risk enhancers. However, inconsistencies in reporting standards and limited data from low-resource settings hinder comprehensive risk stratification. The results underscore the urgent need for standardized antenatal screening protocols, improved maternal health monitoring, and broader implementation of evidence-based interventions. Further research should focus on integrating genetic, biochemical, and ultrasound markers for early identification of high-risk pregnancies. Addressing these gaps is critical not only for reducing fetal mortality but also for improving maternal outcomes and achieving global maternal-fetal health targets.